Mapping the Digital Ecosystem of Muslim-Friendly Tourism: Stakeholder Networks, Sentiment, and Themes on X - Asep Miftahuddin; Juliana Juliana; Lazuardi Imani Hakam; Rizqiana Arifatul Husna; Muhammad Apriandito Arya Saputra; Budhi Pamungkas Gautama (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
The rise of digital communication has reshaped the way tourism stakeholders interact, share information, and influence destination development. Muslim-Friendly Tourism has become one of the fastest-growing segments of the global industry; however, it has rarely been studied through a digital ecosystem lens. This study examines the halal tourism ecosystem by analyzing halal tourism conversations on X (formerly Twitter), mapping stakeholder interaction patterns, public sentiment, emotional responses, and dominant discussion themes. A dataset of 2,000 posts was collected via the SocialX platform between January 30, 2025, and March 30, 2026, and analyzed through an integrated framework combining Social Network Analysis, trend analysis, sentiment and emotion analysis, text clustering, topic modeling, and text network analysis. The network proved highly fragmented with 1,725 nodes, 1,417 directed edges, and 725 communities, reflecting the wide range of stakeholders involved; however, a few influential actors emerged as information brokers linking otherwise separate communities. Sentiment was predominantly neutral (46.75%), with positive sentiment (35.70%) clearly outweighing negative sentiment (17.55%), while happiness dominated the emotional landscape at 88.45%. The thematic analyses returned 14 discussion clusters and 117 topics, and the semantic network revealed three interconnected domains underpinning the ecosystem: the Destination and Policy Ecosystem, the Muslim Traveler Experience Ecosystem, and the Global Halal Travel Ecosystem. These findings extend Digital Ecosystem Theory to Muslim-Friendly Tourism and underscore the role of digital platforms in enabling stakeholder interaction, knowledge exchange, and value co-creation, offering practical guidance for policymakers, destination management organizations, and tourism businesses seeking to strengthen digital engagement and competitiveness